POTENSI PRODUKSI SUSU SAPI PERAH SEBAGAI BAHAN BAKU PRODUK SUSU OLAHAN (Studi Kasus Kabupaten Semarang dan Kabupaten Boyolali) - Rachman Djamal; Singgih Februhardi; Muchson Muchson (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2010)
This research has same purpuses to see : 1) the dairy processing system becames the dairy products (pateurization, milk crackers, milk soap, and dodol susu); 2) the feasibility of business development of processed dairy products; and 3) the adminitration of fresh dairy prodacts trade and processed. This research is a case study by taking two potencial location of dairy that are, Semarang and Boyolali Regency. This reseach is done by observational methods completed by the results of intervews with dairy farmers, processer of processed product, refined products traders and focused group discution(FGD) followed by many releted party with the development of dairy production and dairy product. Primary and secondary data is analysized bay descriptive and statistic. The research result shows that the dairy production produced by breeders for last 10 year in Semarang regency increases with the frend of production, Y= 20.583,571 + 233,157 X, while it tends to decline in Boyolali that is , Y = 30.386,235 - 124,655 X. The dairy production system in the research area leads to main busisness with pattern producing milk. Dairy quality produced is varies, started from BJ (density) fat rate, protein rate, acidity of milk lactose rate that is relativity well except BJ and SNF (Solit non Fat) still under SNI. The population effect to dairy production in the research area is unreal (P>0,05). It is caused by lots of factors, that are education and breeder experience, business management, seed of cow, and tendency of business orientation to fattening. The processed dairy products such as milk crackers, milk crust, dodol susu and others ar not much developed but they have beenattepted to develop by people, one of the developed dairy products haring market target is pasteurization produced by CV. Citra Nasional. The marketing of fresh dairy to consumers is done by retailers, the processed dairy product such as milk crackers, milk crust, milk candy and others are done by breeder family chame industry that is generally produced in accordance with the castomers demand and thay haven’t been commercially attempted. The feasibility of business developmet of processed dairy products gives enough advantage and development appropriately. Trade system and marketing of fresh dairy still rely on KUD, though there has been brokers or collectors that joint to market dairy to GKSI (Indonesian Dairy Cooperative Joint) and IPS (Dairy Processing Industry).